Isu Kepatuhan Syariah pada Akad Musyarakah Mutanaqishah di Indonesia - Sry Muliyani; Mawaddah Rachman; Eka Dewintara; Rahman Ambo Masse (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
The development of Islamic financial institutions in Indonesia has increased quite a bit from year to year. This is because people's interest in saving is quite high in Islamic financial institutions. Interest-based conventional financial institutions can be compared with products from Islamic financial institutions. For example, cooperation-based sharia banking products with a "profit and loss sharing" system such as musyarakah and mudharabah contracts. The implementation of cooperation products with this musyarakah contract did not show significant growth so that the innovation of the musyarakah contract was implemented which resulted in a Musyarakah Mutanaqishah contract in accordance with National Syari'ah Council Fatwa No: 08/DSN-MUI/IV/2000 Concerning Musyarakah Financing and Council Fatwa National Sharia No: 73/DSN-MUI/XI/2008 Concerning Musyarakah Mutanaqisah. The purpose of writing this paper is to analyze the issue of sharia compliance in musyarakah mutanaqishah contracts practiced in sharia banking products in Indonesia. These issues consist of sharia issues, legal issues and operational issues according to the musyarakah and musyarakah mutanaqishah product standard books published by the Financial Services Authority (OJK) in 2016. The results of the analysis in this paper show that first, sharia issues generally occur in this issue. is the existence of "two contracts in one item" where the rental and purchase contracts are agreed at the same time. Second, legal issues related to the existence of different perspectives between fiqh rules and Indonesian positive law related to the recording of ownership certificates. And the third issue, an operational issue where there is price independence when a financing contract with a musyarakah scheme is made that requires a transfer of ownership.